The communicative space in computer games: retrospective analysis - Grigorieva, Anna O. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
In this article historical dynamics of formation and the subsequent development of a computer game as a new virtual work of art genre is analysed. Stages of a computer game development in the developer – technical tool – game audience system, based on specifics of social communication between them are distinguished. Intrinsic characteristics of a computer game in contrast to the games realised by means of the technical device are distinguished. The generalised definition of the concept «computer game» is given.
Keywords: computer games; video games; arcade machine; social communication; cybersports; game audience